Порівняльна оцінка стандартного та мінімально інвазійного методів виконання гемітиреоїдектомії за фолікулярних пухлин щитоподібної залози - Чернишов, С. В. (Clinical Endocrinology and Endocrine Surgery, 2013)
A comparative evaluation of the surgery on the thyroid gland in the volume of the standard hemithyroidectomy by Kocher’s access and minimally invasive approach was done. It was determined that minimally invasive approach has significant advantages, such as: shorter duration of the operations, fewer fluid to drain, a smaller percentage of postoperative edema of the scar, the absence of seroma. Significantly lower number of patients in the minimally invasive access needed for analgesia on the second day after the operation. Reducing the above indicators has led to a decrease in the average postoperative hospital-days stay in 3.7 times. Noteworthy as well as higher subjective assessment of patients form scar at 3 months after surgery in the group with a minimally invasive access.